2011
DOI: 10.3109/02699052.2011.608209
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of soccer heading to computerized neurocognitive performance and symptoms among female and male youth soccer players

Abstract: The current findings did not support a relationship between soccer heading and computerized neurocognitive performance and symptoms. The researchers suggest that any purported effects of soccer heading in youth are subtle and may affect only a small number of athletes. The reported sex differences in heading exposure warrant further attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 31 publications
(48 reference statements)
2
39
0
Order By: Relevance
“…Age range for youth football players was 10–1318 and 13–18 12. The category ‘High school/college’ includes the ‘interscholastic’ as well.…”
Section: Resultsmentioning
confidence: 99%
“…Age range for youth football players was 10–1318 and 13–18 12. The category ‘High school/college’ includes the ‘interscholastic’ as well.…”
Section: Resultsmentioning
confidence: 99%
“…2,22 In the collegiate and professional literature, debate exists over concussion risk from heading alone vs contact with another player or object during heading. Several studies 23,24 found that purposeful heading did not result in neurocognitive deficits, including among 13-to 18-year-old players. Barnes et al 25 reported that more than half of the elite women players experienced headaches after heading, some lasting up to 25 days, and 2 reported amnesia.…”
Section: Discussionmentioning
confidence: 99%
“…20,[34][35][36][37] Prior work suggests that person-to-person collisions are the dominant cause of concussion in high school players. 22 The latter conclusion, however, was based on sideline observer detection, definition, and reporting of concussion, where overt events will stand out.…”
mentioning
confidence: 99%